2004
DOI: 10.3354/dao059171
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of the polyphenols resveratrol, mangiferin and (–)-epigallocatechin-3-gallate on the scuticociliate fish pathogen Philasterides dicentrarchi

Abstract: This study investigated the in vitro effects of the polyphenols resveratrol, mangiferin and (-)-epigallocatechin-3-gallate (EGCG) on the histiophagous ciliate Philasterides dicentrarchi, which causes fatal scuticociliatosis in farmed turbot Scophthalmus maximus L. Of the 3 polyphenols, resveratrol showed strongest antiprotozoal activity, reducing ciliate density after 1 wk culture by, on average, 91% at 50 µM, and 96% at 500 µM. EGCG reduced ciliate density by, on average, 93% at 500 µM, with no significant ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 22 publications
0
44
0
Order By: Relevance
“…The effects of RESV and MDZ on the in vitro growth of T. vaginalis were determined as previously described, with minor modifications (18). For all experiments, stock solutions of RESV and MDZ were prepared in dimethyl sulfoxide (DMSO), to a concentration of 100 mM, and stored away from light at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of RESV and MDZ on the in vitro growth of T. vaginalis were determined as previously described, with minor modifications (18). For all experiments, stock solutions of RESV and MDZ were prepared in dimethyl sulfoxide (DMSO), to a concentration of 100 mM, and stored away from light at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…RESV, which is found naturally in grapes and red wine (14), acts as a precursor for stilbene compounds of higher fungotoxicity that accumulate in grapevine as a result of infection or stress (15). RESV has also been shown to be active against bacteria, fungi, protozoa, and viruses (16)(17)(18)(19)(20)(21)(22). In addition to its antimicrobial activity, RESV has also attracted attention on the basis of its health benefits to humans, which include anti-inflammatory effects; reduced risks of cardiovascular disease, cancer, obesity, diabetes, and neurodegenerative diseases; and also extension of life span by mimicking the caloric restriction effect (23).…”
mentioning
confidence: 99%
“…Several lines of evidence indicate that Resveratrol is also capable of immunomodulatory, antioxidative, anti-apoptotic and anti-inflammatory functions [14,20,29,44]. Curcumin (diferuloylmethane), a dietary non-toxic pigment in curry, acts as a potent inhibitor of nuclear transcription factor jB (NF-jB)-activation in several cell types [10,47,53].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated the low toxicity of certain polyphenols in mice and humans (García et al 2003). It has therefore been hypothesized that these polyphenols would not be toxic to fish when used under in vivo conditions (Leiro et al 2004). Suzuki et al (2006) studied the efficacy and safety of GTE in salmonids under hatchery conditions, but the concentrations used were much lower than the efficient concentration tested in the present study against C. irritants.…”
Section: Resultsmentioning
confidence: 90%
“…EGCG comprises 14% of GTE, and it was shown that an application of pure EGCG was able to reduce I. necator infections (Suzuki et al 2006). Leiro et al (2004) showed that in vitro exposure to 500 µM of EGCG over 1 wk reduced the population density of the ciliate Philasterides dicentrarchi Dragesco et al, 1995 by 93%. In the present study, EGCG managed to kill all theronts when applied at 50, 250 or 500 mg l -1 over a period of 3 h, whereas its efficacy was considerably lower when application times were shorter and doses were lower (Table 1).…”
Section: Resultsmentioning
confidence: 99%